2016
DOI: 10.1002/maco.201508795
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of pitting corrosion on the mechanical properties of steel reinforcement

Abstract: 6 and tensile behavior of reinforcing bars are studied via experimental tests and 7 analytical modeling, respectively. Hemispherical indentation is mechanically 8 produced on the reinforcing steel to simulate pitting corrosion. Static tensile 9 tests are conducted for 9 non-corroded and 54 pitting corrosion-simulated bars 10 with varying levels of pit sizes using two different test setups. This investigation 11 has resulted in clear quantification of the relationship between the degree of 12 corrosion and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Pitting corrosion affects the load‐carrying capacity of a structure and strongly reduces its deformation capacity, as was experimentally verified by several studies 2,6–8 . This effect is mainly caused by strain localisation due to cross‐section loss.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Pitting corrosion affects the load‐carrying capacity of a structure and strongly reduces its deformation capacity, as was experimentally verified by several studies 2,6–8 . This effect is mainly caused by strain localisation due to cross‐section loss.…”
Section: Introductionmentioning
confidence: 70%
“…Pitting corrosion affects the load-carrying capacity of a structure and strongly reduces its deformation capacity, as was experimentally verified by several studies. 2,[6][7][8] This effect is mainly caused by strain localisation due to cross-section loss. It is particularly relevant for statically indeterminate structures requiring moment redistributions (e.g., multi-span continuous girders) or in the case of deformation-dependent loading (e.g., earth pressure action on cantilever retaining walls).…”
Section: Introductionmentioning
confidence: 99%
“…It rarely accounts for the most severe location of a corrosion pit. It has been shown that the minimum cross section of a local corrosion pit is the most critical site for fatigue crack initiation, propagation, and final fracture due to stress concentration and cyclic fatigue loads [19][20][21]. As a result, the average treatment can introduce additional uncertainty into fatigue life prediction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transport mechanism of chloride ions through cement‐based materials has been fully studied . Therefore, it is possible to predict the initial time for the depassivation of steel rebars caused only by chloride ingress …”
Section: Introductionmentioning
confidence: 99%
“…[4] Therefore, it is possible to predict the initial time for the depassivation of steel rebars caused only by chloride ingress. [3,5] For most reinforced concrete buildings, the carbonation process of concrete is inevitable [6][7][8] . And it leads to two major changes in the chemical environment of concrete pore solutions.…”
Section: Introductionmentioning
confidence: 99%